SLAM-SAP-Fyn: Old Players with New Roles in iNKT Cell Development and Function - Bahal, Devika (Int J Mol Sci, 2019)
Invariant natural killer T (iNKT) cells are a unique T cell lineage that develop in the thymus and emerge with a memory-like phenotype. Accordingly, following antigenic stimulation, they can rapidly produce copious amounts of Th1 and Th2 cytokines and mediate activation of several immune cells. Thus, it is not surprising that iNKT cells play diverse roles in a broad range of diseases. Given their pivotal roles in host immunity, it is crucial that we understand the mechanisms that govern iNKT cell development and effector functions. Over the last two decades, several studies have contributed to the current knowledge of iNKT cell biology and activity. Collectively, these studies reveal that the thymic development of iNKT cells, their lineage expansion, and functional properties are tightly regulated by a complex network of transcription factors and signaling molecules. While prior studies have clearly established the importance of the SLAM-SAP-Fyn signaling axis in iNKT cell ontogenesis, recent studies provide exciting mechanistic insights into the role of this signaling cascade in iNKT cell development, lineage fate decisions, and functions. Here we summarize the previous literature and discuss the more recent studies that guide our understanding of iNKT cell development and functional responses.